Voltage versus Power Factor Regulation for enhancement of renewable generation capacity - Ahmadi,AR; Green,TC (2010)
The connection of Distributed Generators (DGs) to distribution network creates technical concerns for Distribution Network Operators (DNOs) which primarily include power flow management, loss increase and voltage management problems. Active Network Management (ANM) system provides monitoring and control of the distribution network as well as providing the infrastructure and technology for full integration of DGs to the distribution network. Optimal Power Flow (OPF) is a valuable tool in providing optimal control solutions for active network management system applications. In this paper, Terminal Voltage Regulator Mode (TVRM) and fixed Power Factor Regulation Mode (PFRM) were incorporated in the main optimisation routine to extract the maximum real power output capacity. The main contribution was to test different droop characteristics including one with local voltage regulator dead-bands associated to a particular DG. The DG operation methods of PFRM and TVRM are then compared together. Numerical result obtained from tests on two U.K. representative distribution networks show that TVRM has the potential in offering more capacity exploitation and improving network flexibility for additional DG connection.